Diamond Deposition on Graphite in Hydrogen Microwave Plasma - Zhu, Jiaqi; Yao, Kaili; Dai, Bing; Ralchenko, Victor; Shu, Guoyang; Zhao, Jiwen; Liu, Kang; Yang, Lei; Bolshakov, Andrey; Han, Jiecai (Journal of Coating Science and Technology, 2018)
Hydrogen plasma etching of graphite generates radicals that can be used for diamond synthesis by chemical vapor deposition (CVD). We studied the etching of polycrystalline graphite by a hydrogen microwave plasma, growth of diamond particles of the non-seeded graphite substrates, and characterized the diamond morphology, grain size distribution, growth rate, and phase purity. The graphite substrates served simultaneously as a carbon source, this being the specific feature of the process. A disorder of the graphite surface structure reduces as the result of the etching as revealed with Raman spectroscopy. The diamond growth rate of 3 – 5 µm/h was achieved, the quality of the produced diamond grains improving with growth time due to inherently nonstationary graphite etching process